Development of Polymeric Materials to Inhibit Bacterial Quorum Sensing - Cavaleiro, Eliana Marisa dos Santos (Cranfield University, 2014)
Bacterial infections are an increasing problem for human health. In fact, an increasing number of infections are caused by bacteria that are resistant to most antibiotics and their combinations. A new solution to fight bacteria and infectious diseases, without promoting antimicrobial resistance, is required. A promise strategy is the disruption or attenuation of bacterial Quorum Sensing (QS), a refined system that bacteria use to communicate. In a QS event, bacteria produce and release specific small chemicals, signal molecules - autoinducers (AIs) - into the environment. AIs regulate gene expression as a function of cell population density. Phenotypes mediated by QS (QS- phenotypes) include virulence factors, toxin production, antibiotic resistance and biofilm formation. In this work, two polymeric materials (linear polymers and molecularly imprinted nanoparticles) were developed and their ability to attenuate QS was evaluated. Both types of polymers should be able to adsorb bacterial signal molecules, limiting their availability in the extracellular environment, with expected disruption of QS. Linear polymers were composed by methyl methacrylate as backbone and itaconic acid or methacrylic acid as functional monomer. IA and MAA monomers were identified by computer modelling to have strong interactions with the AIs produced by Gram-negative bacteria. Cont/d.
Keywords: Quorum Sensing; Linear Polymers; Molecularly Imprinted Nanoparticles; Vibrio fischeri; Aeromonas hydrophila